How to Improve the Antioxidant Defense in Asphyxiated Newborns-Lessons from Animal Models - Hanna Kletkiewicz; Maciej Klimiuk; Alina Woźniak; Celestyna Mila-Kierzenkowska; Karol Dokladny; Justyna Rogalska (MDPI AG, 2020)
Oxygen free radicals have been implicated in brain damage after neonatal asphyxia. In the early phase of asphyxia/reoxygenation, changes in antioxidant enzyme activity play a pivotal role in switching on and off the cascade of events that can kill the neurons. Hypoxia/ischemia (H/I) forces the brain to activate endogenous mechanisms (e.g., antioxidant enzymes) to compensate for the lost or broken neural circuits. It is important to evaluate therapies to enhance the self-protective capacity of the brain. In animal models, decreased body temperature during neonatal asphyxia has been shown to increase cerebral antioxidant capacity. However, in preterm or severely asphyxiated newborns this therapy, rather than beneficial seems to be harmful. Thus, seeking new therapeutic approaches to prevent anoxia-induced complications is crucial. Pharmacotherapy with deferoxamine (DFO) is commonly recognized as a beneficial regimen for H/I insult. DFO, via iron chelation, reduces oxidative stress. It also assures an optimal antioxidant protection minimizing depletion of the antioxidant enzymes as well as low molecular antioxidants. In the present review, some aspects of recently acquired insight into the therapeutic effects of hypothermia and DFO in promoting neuronal survival after H/I are discussed.